Legalising the illegal: an assessment of the Dispensation of Zimbabweans Project (DZP) and Zimbabwe Special Dispensation Permit (ZSP) regularisation projects - Bimha, Primrose Zvikomborero Joylyn (Department of Political Studies, 2017)
Since the late 1990s economic insecurity and political uncertainty have continued to worsen in Zimbabwe. Zimbabwe's economy plunged into deep crisis in the early 2000s owing to failed fiscal policies and the highly criticised 'Fast-track' land reform program. Election related violence between 2002 and 2013 resulted in a state of insecurity thereby leading to an exodus of Zimbabwean migrants. An unprecedented influx of Zimbabwean migrants to South Africa (SA) led to high levels of illegal migration and the clogging up of the asylum seeker management system in the early 2000s. In 2009, SA launched the Dispensation of Zimbabweans Project (DZP) in order to achieve four main objectives: to reduce pressure on the asylum management system, to curb the deportation of illegal Zimbabwean migrants, to regularise Zimbabweans who were residing in SA illegally and to provide amnesty to Zimbabweans who had obtained South African documents fraudulently. The DZP was considered a success and a successor permit, the Zimbabwe Special Dispensation Permit (ZSP), was launched in 2014 to allow former DZP applicants to extend their stay in South Africa. Using government publications, parliamentary debates, non-governmental organization (NGO) and media reports it was found that the DZP reduced pressure on the asylum seeker management system while deportation figures dropped significantly. It was also found that, less than 6% (250 000) of an estimated 1,5 million undocumented migrants were documented during the regularisation processes. The DZP and ZSP projects complemented South Africa's highly restrictive approach to migration management and jealous safeguarding of access to permanent residence and citizenship. The regularisation projects also enabled the South African government to show sympathy towards Zimbabweans who were forced to migrate to South Africa by recognising that they could not return home as long as the situation back home remained unchanged.